Functional skills gap: The role of artificial intelligence and teachers' digital competence in South Pakistani Islamic schools - Muhammad Kashif Majeed; Tunku Badariah Ahamad (EDUCARE Journal of Primary Education, 2025)
The gap in teachers' functional skills in utilizing artificial intelligence and digital competencies remains a major issue in Islamic schools in Southern Pakistan. Gender variations show differences in technological adaptation abilities, so that AI integration has not had an equal impact on improving functional pedagogical practices. This study aims to analyze the influence of digital competence and AI use on the functional skills of Islamic school teachers in Southern Pakistan and to examine the moderating role of gender in this relationship. This quantitative research with a cross-sectional survey design involved 450 Islamic school teachers in South Punjab using a Likert scale questionnaire to analyze the relationship between digital competence, AI use, and functional skills, as well as to identify gender-based differences in technology integration. This study concludes that the integration of AI and digital competence in Islamic education in Southern Pakistan is influenced by gender factors, with female teachers being more effective at converting AI into functional teaching skills. These findings call for gender-sensitive, inclusive, and sustainable professional development policies. This research contributes by strengthening empirical evidence of the role of gender in AI integration, enriching gender-perspective organizational theory, and offering a conceptual basis for gender-sensitive professional development policies for Islamic teachers.